Analyses of Latvian national geodetic reference system - Liepins, Ivars; Kalinka, Maris (International Conference “Environmental Engineering”, 2017)
National geodetic reference system is base for geodetic and geospatial data and information obtaining, maintenance and distribution in common reference system in country. It means, that it must be as accurate as possible and lockstep with time. Latvian national geodetic reference system (LNGRS) derives from Soviet Union geodetic reference system at beginning of 90-ties last century. Development of LNGRS was done as historical continuation of practice to use height, coordinates, Earth gravitational and geomagnetic systems and national networks. For coordinates was established new Latvian geodetical coordinate system using one week campaign data of GPS NAVSTAR. Heights were kept in Baltic normal height system epoch 1977. Earth gravitational system was established newly by absolute gravimetric measurements. Geomagnetic system was developed as repeat station system. Earth is constantly change system internally and outwardly More growing use of GIS and GNSS in agriculture, construction, logistic, military and everyday life put new challenge for LNGRS and it reliability to actual situation in top level. Main goal of publication is to analyse all aspects of LNGRS against nowadays criteria and requirements of dynamic national geodetic reference system. Results of analyses show feeble and powerful sides of LNGRS.
Keywords: national geodetic references system definition; realization; management